2022
DOI: 10.1108/ijem-03-2022-0106
|View full text |Cite
|
Sign up to set email alerts
|

Social factors impacting student’s choice of institution for higher studies in India

Abstract: PurposeThis study intends to build up a thorough understanding of social factors that largely influence students’ decision-making to opt institution for higher studies in India.Design/methodology/approachThis descriptive research follows two sequential phases consisting of the literature review to identify social factors and validate the factors through the questionnaire method. Factor analysis was applied to identify the various factors that influence the student’s institution choice.FindingsThe research work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Our education system should understand the psychological and behavioral aspects of students. 20 It has been suggested that the higher education system must thoroughly examine how students think about suicide and empathize with them, to solve this issue. 21 Suicidality is studied in isolation from the situations in which students live, which means that others are looking at it through the incorrect end of the telescope.…”
Section: Discussionmentioning
confidence: 99%
“…Our education system should understand the psychological and behavioral aspects of students. 20 It has been suggested that the higher education system must thoroughly examine how students think about suicide and empathize with them, to solve this issue. 21 Suicidality is studied in isolation from the situations in which students live, which means that others are looking at it through the incorrect end of the telescope.…”
Section: Discussionmentioning
confidence: 99%
“…Universities should be held accountable for helping students succeed in the classroom and retaining them until graduation. Several studies have shown that a university's commitment to student success after graduation is crucial (Srivastava and Dhamija, 2022; Yang et al , 2020). However, as previous research has shown, many potential students today seek more intrinsic values from their college experience, such as deeper relationships with faculty and staff and feelings of inclusion and belonging (Bozeman and Eadens, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The college choice is a multi-stage intricate process where a person aspires to endure formal education beyond school followed by a later decision on enrolling in a particular educational institution, college or university (Hossler and Gallagher, 1987; Hossler et al ., 1989). There are various determinants that drive the process of decision-making to opt institution for higher education (Srivastava and Dhamija, 2022a, b), so this process has become an important policy concern.…”
Section: Theoretical Background and Development Of Hypothesismentioning
confidence: 99%
“…For their career decisions, students typically follow a pattern of behavior in which they seek the approval of their parents, society and peer groups. The prior research works strongly inquire about the rationale behind why students submit to such social pressures (Srivastava and Dhamija, 2022a, b). It is crucial to present the pertinent social influence perspectives and theories supporting the acceptance of influence to investigate the impacts of these social influences on the students.…”
Section: Introductionmentioning
confidence: 99%